Direct and indirect costs of dinitrogen fixation in Crocosphaera watsonii WH8501 and possible implications for the nitrogen cycle - Großkopf, Tobias; LaRoche, Julie (Frontiers in Microbiology, 2012)
The recent detection of heterotrophic nitrogen (N2) fixation in deep waters of the southern Californian and Peruvian OMZ questions our current understanding of marine N2 fixation as a process confined to oligotrophic surface waters of the oceans. In experiments with Crocosphaera watsonii WH8501, a marine unicellular diazotrophic (N2-fixing) cyanobacterium, we demonstrated that the presence of high nitrate concentrations (up to 800 µM) had no inhibitory effect on growth and N2 fixation over a period of two weeks. In contrast, the environmental oxygen concentration significantly influenced rates of N2 fixation and respiration, as well as carbon and nitrogen cellular content of C. watsonii over a 24 hour period. Cells grown under lowered oxygen atmosphere (5%) had a higher nitrogenase activity and respired less carbon during the dark cycle than under normal oxygen atmosphere (20%). Respiratory oxygen drawdown during the dark period could be fully explained (104%) by energetic needs due to basal metabolism and N2 fixation at low oxygen, while at normal oxygen these two processes could only account for 40% of the measured respiration rate. Our results revealed that under normal oxygen concentration most of the energetic costs during N2 fixation (~60%) are not derived from the process of N2 fixation per se but rather from the indirect costs incurred for the removal of intracellular oxygen or by the reversal of oxidative damage (e.g. nitrogenase de novo synthesis). Theoretical calculations suggest a slight energetic advantage of N2 fixation relative to assimilatory nitrate uptake for heterotrophic and phototrophic growth, when oxygen supply is in balance with the oxygen requirement for cellular respiration (i.e. energy generation for basal metabolism and N2 fixation). Taken together our results imply the existence of a niche for diazotrophic organisms inside oxygen minimum zones, which are predicted to further expand in the future ocean.